Leveraging Experiential Learning to Foster University Students’ Proficiency in Engaging with People with Disabilities - Folgueras, Xazmín; Viera-Abelleira, Marcelo; Pérez-Campos, Carlos; González-García, Rómulo J. (Physical Education Theory and Methodology, 2023)
Study purpose. Inclusive education, acknowledged as a fundamental human right, is aimed at enhancing the participation of all students and mitigating social and educational exclusion. Physical Education is identified as a vital instrument that fosters specific training on disability and inclusion, thereby ameliorating attitudes towards disability. The objective of this study is to scrutinize the perception of experiential learning and inclusive physical activity among students. Materials and methods. An inclusive physical activity program for students pursuing a degree in Early Childhood and Primary Education was designed. The program proposes five sessions of inclusive physical activity and accommodates 30 adult users with intellectual disability. To analyse the reliability and validity of a scale that measures students’ perception of experiential learning, descriptive statistics, reliability analysis, exploratory and confirmatory factor analysis were used to assess the effectiveness and inclusivity of the scale. Results. The validity and reliability of a scale that facilitates the analysis of students’ perceptions of learning derived from inclusive experiences is presented and the results are adequate for its usability. In addition, it is shown that experiential learning increases the perception towards the acquisition of disability-related competences among university students. Conclusions. This scale essentially allows a comprehensive analysis of students’ perception of learning that emerges from inclusive experiences. It is demonstrated that experiential learning enhances students’ perception regarding the attainment of competencies related to disability. These findings underscore the importance of inclusive learning experiences in the training of future educators.